Effect of monodisperse mesoporous bioactive glass spheres (MBGs) on the mechanical properties and bioactivity of dental composites. (June 2023) - Wang, Yueyue; Bai, Xingxing; Li, Huaizhu; Kong, Hongxing; Yao, Xiaohong
Abstract: Secondary caries is one of the main reasons for the failure of dental resin composites, and adding bioactive fillers such as bioactive glass and amorphous calcium phosphate to the resin composites has been proved to be an effective solution for this problem. In the present study, we investigated the effect of monodisperse mesoporous bioactive glass spheres (MBGs) we prepared on the mechanical properties and bioactivity of dental resins. The results revealed that compared with traditional bioactive glass (BG), MBGs fillers significantly enhanced the mechanical properties of the dental resin composites, whether they were added alone or as functional fillers together with nonporous silica particles. The dental resins filled with bimodal fillers (mass ratio of MBGs: nonporous silica = 10:50, total filler loading 60 wt%) exhibited the best mechanical performance. Their flexural strength was 37.66% higher than the samples with BG at the same filling proportion. Furthermore, the prepared MBGs possessed excellent monodispersity and sufficient apatite formation performance, and the biocompatibility of the composites were also improved by MBGs fillers. These suggest the potential use of the prepared MBGs as multifunctional fillers for the improvement of the performance of dental resins. Highlights: Monodisperse mesoporous bioactive glass spheres (MBGs) could be thoroughly dispersed in the resin matrix. The mechanical properties of the dental resin composites were significantly improved by MBGs fillers. The dental resin composites containing MBGs processed sustained calcium ion release ability and improved biocompatibility.